Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
Keywords: Archives; Musée McCord; Musées

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

Révolution dans les archives...et dans la reconstitution du passé - Deslandres, Dominique (Les cahiers des Dix, 2023)
Keywords: Archives

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
Keywords: Archives; Archives municipales

Les procès en sorcellerie, des archives longtemps négligées : le cas de Montréal - Pettigrew, Stéphanie (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Archives; Tribunaux

''Au-delà du syndrome de la «citation payante»'': les archives vivantes et la recherche réciproque en histoire orale - High, Steven (Revue d'histoire de l'Amérique française, 2015)
Keywords: Archives; Histoire

L'odyssée des archives de la Société Historique de Montréal - Robert, Mario (Montréal en tête, 2019)
Keywords: Archives; Société historique de Montréal

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

Théâtre à Montréal, 1825-1930: un récit visuel mettant en scène des documents patrimoniaux - Léger, Danielle (Archives, 2019)
Keywords: Cartes et plans; Histoire; Patrimoine; Théâtre

Historienne, mentore, libre-penseuse: réflexions autour de l'oeuvre d'Andrée Lévesque - Fahrni, Magda (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Archives; Femmes; Histoire

Identities, Communities, and the Infrastructures of History: Creating Canadian Jewish Archives in the 1930s and the 1970s - Menkis, Richard (History, Memory, And Jewish Identity, 2015)
Keywords: Congrès juif canadien; Histoire; Juifs

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Regards sur une Bible hébraïque, une Bible polyglotte et une Bible de Genève conservées par Bibliothèque et Archives nationales du Québec - Crevier Denommé, Isabelle (Ouvrages phares de la Réforme & de la Contre-Réforme dans les collections montréalaises, 2014)
Keywords: Bibliothèque nationale

À la découverte du Fonds Albéric Bourgeois (1876-1962): thématiques d'une société en transformation, 1899-1957 - Hardy, Dominic; Godin-Laverdière, Julie-Anne; Perron, Nancy (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Archives; Bourgeois, Albéric; Caricature; Histoire

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées